1970
DOI: 10.1161/01.res.27.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Local Regulation of Vascular Cross Section during Changes in Femoral Arterial Blood Flow in Dogs

Abstract: Diameters of the exposed femoral artery of anesthetized dogs were continuously measured with ultrasonic elements of lead zirconate titanate. In 13 of 16 dogs vascular diameters increased following a sudden increment in arterial blood flow induced by the injection of vasodilat i ng agents (acetylcholine, histamine) peripheral to the recording level, by opening an arteriovenous shunt, or after tetanic stimulation of die sciatic nerve. The dilatation response occurred despite slight reductions in femoral blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(56 citation statements)
references
References 13 publications
4
52
0
Order By: Relevance
“…For instance, studies have shown that hand warming has no effect on brachial artery diameter when flow is not allowed to rise 48,50,116) . Furthermore, pharmacological blockade of the autonomic nervous system has no effect on radial artery FMD in response to hand warming 116) , consistent with animal studies showing that FMD is preserved after surgical or pharmacological denervation 122,123) . A recent meta-analysis by Inaba et al 11) , which was subsequently re-analyzed by Green et al 124) , assessed the CVD prognostic strength of FMD by conducting a meta-analysis of observational studies that examined the association between brachial artery FMD and future cardiovascular events.…”
Section: Transient Versus Steady-state Shear Stresssupporting
confidence: 76%
“…For instance, studies have shown that hand warming has no effect on brachial artery diameter when flow is not allowed to rise 48,50,116) . Furthermore, pharmacological blockade of the autonomic nervous system has no effect on radial artery FMD in response to hand warming 116) , consistent with animal studies showing that FMD is preserved after surgical or pharmacological denervation 122,123) . A recent meta-analysis by Inaba et al 11) , which was subsequently re-analyzed by Green et al 124) , assessed the CVD prognostic strength of FMD by conducting a meta-analysis of observational studies that examined the association between brachial artery FMD and future cardiovascular events.…”
Section: Transient Versus Steady-state Shear Stresssupporting
confidence: 76%
“…These results suggest that luteal NO has dual functions according to the luteal phase. Shear stress is generated when the blood flow volume and blood pressure are increased [40]. Shear stress is the frictional tangential force imposed on the vessel wall when blood flows through the vessel.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that an NO donor inhibits progesterone secretion [17] and induces apoptosis [39] of mid luteal cells. These results suggest that luteal NO has dual functions according to the luteal phase.Shear stress is generated when the blood flow volume and blood pressure are increased [40]. Shear stress is the frictional tangential force imposed on the vessel wall when blood flows through the vessel.…”
mentioning
confidence: 99%
“…This phenomenon is directly dependent upon changes in flow, rather than pressure, and is mediated by a nonneurogenic local mechanism (2). The mechanism of flowmediated vasodilation is not well understood.…”
Section: Introductionmentioning
confidence: 99%